Upaya Perlindungan Hukum terhadap Kreditur atas Debitur Wanprestasi dalam Perjanjian Kredit pada Masa Pandemi Covid-19 - Ni Made Mirah Dwi Lestari; I Nyoman Putu Budiartha; Ni Gusti Ketut Sri (Jurnal Interpretasi Hukum, 2022)
Default can occur either due to intentional factors or factors beyond human capabilities, such as what happened to the Amerta Sedana Wisata cooperative, a debtor does not fulfill his agreement by being in arrears for debt payments of up to 10 months. This study aims to reveal legal protection efforts against creditors for defaulting debtors in credit agreements during the Covid-19 pandemic. The research method carried out in this writing is using empirical legal research with a statutory approach (The Statute Approach). The results obtained in this study are forms of legal protection that can be carried out in resolving defaults committed by debtors, namely by using preventive legal protection and repressive legal protection. Legal protection for creditors has been regulated based on the Civil Code Articles 1131 and 1132. In the credit agreement the Amerta Sedana Wisata Savings and Loans Cooperative more often uses non-litigation channels to resolve existing default or non-performing credit problems. Based on the discussion that has been described, the conclusion in this study is that preventive action is an action or effort taken before the occurrence of a dispute and violation of norms. Preventive legal protection is applied by following regulations. Researchers hope that in borrowing money or credit, they should understand correctly how the risks will arise in the future if there is a dispute that arises due to default.